Co-payments and equity in care: enhancing hospitalisation policy for Palestine refugees in Lebanon - Sara Valente de Almeida; Gloria Paolucci; Akihiro Seita; Hala Ghattas (BMC, 2022)
Abstract Background This paper measures the impact of introducing a 10% co-payment on secondary care hospitalization costs for Palestine refugees living in Lebanon (PRL) in all UNRWA contracted hospitals, except for the Red Crescent Society. This ex-post analysis provides a detailed insight on the direction and magnitude of the policy impact in terms of demand by hospital type, average length of stay and treatment costs. Methods With a complete population episode level dataset, we use multinomial logit, negative binomial, and linear models to estimate impacts on the different dependent variables, controlling for disease, patient and hospital characteristics. Results After the implementation patients were at least 4 pp (p <0.01) more likely to choose a Red Crescent Society hospital for secondary care, instead of one with co-payment. Average length of stay was not affected in general, despite the increase in control at all UNRWA contracted hospitals. Except for the decrease in UNRWA contribution, did not find a statistically significant impact of the co-payment on costs, nor for the provider or for the patient. Findings suggest that introducing a 10% co-payment for secondary hospital care had an impact on patients' health care budget, leading to demand shifts towards cheaper options - i.e., patients had to chose care based on financial constraints rather than on their treatment preferences. Conclusion Before changing healthcare payment schemes in different types of hospitals, facilities offering free of charge treatment should be assessed and prepared for potential demand shifts to avoid overcapacity and the collapse of health care services for such a fragile population. In addition, exemptions from co-payments should be considered for patients with severe health conditions and financial constraints, who, according to our results, are the most likely to change their pattern of care due to an increase in treatment costs.